2014
DOI: 10.1016/j.bpj.2013.11.3506
|View full text |Cite
|
Sign up to set email alerts
|

A Lipid Bound Actin Meshwork Organizes Liquid Phase Separation in Model Membranes

Abstract: Substructure within the liquid-ordered phase of lipid bilayers is reported, composed of saturated hydrocarbon chains packed with local hexagonal order, separated by interstitial regions enriched in cholesterol and unsaturated chains. The structure, identified during 10 msec all-atom molecular dynamics simulation of liquid-ordered/liquid-disordered coexistence (Lo/Ld), is confirmed by comparison to 2H NMR quadropolar splittings. The balance of cholesterolrich to local hexagonal order is proposed to control the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
87
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(97 citation statements)
references
References 0 publications
10
87
0
Order By: Relevance
“…To our knowledge, this is the first time that such a reconstituted active composite system has been described. Our results suggest that the actin cortex may influence plasma membrane organization not only through the interaction of lipids and proteins with a stable actin meshwork (9,42) or polymerizing actin (40,44), but also through the flows of actin filaments generated by myosininduced stresses. Importantly, the flows of myosin-driven short actin filaments influence only those membrane components (proteins and lipids) that can bind to actin such as HYE, whereas the mutant HYE(R579A) and the inert lipid RhoPE do not show a change in their dynamics.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…To our knowledge, this is the first time that such a reconstituted active composite system has been described. Our results suggest that the actin cortex may influence plasma membrane organization not only through the interaction of lipids and proteins with a stable actin meshwork (9,42) or polymerizing actin (40,44), but also through the flows of actin filaments generated by myosininduced stresses. Importantly, the flows of myosin-driven short actin filaments influence only those membrane components (proteins and lipids) that can bind to actin such as HYE, whereas the mutant HYE(R579A) and the inert lipid RhoPE do not show a change in their dynamics.…”
Section: Discussionmentioning
confidence: 85%
“…After addition of polymerized actin, myosin II was added to the chamber in ATP-containing buffers and appropriate salt conditions to generate minifilaments (51). Phasesegregating lipid mixtures of multiple lipid species and cholesterol were prepared in chloroform, deposited on experimental chambers formed on freshly cleaved mica supports (∼100-μm thickness), and rehydrated for bilayer formation (42). Fluorescence imaging was carried out on a custom-designed total internal reflection fluorescence microscope, and electron microscopy on myosin II filaments was performed following established protocols (71).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, syntaxin-1 molecules have been shown to concentrate under docked vesicles before fusion, suggesting that a pool of plasma membrane syntaxin-1 can be recruited by an unknown mechanism under SVs 43 . Another possible contributing factor could involve translocated actin exerting an effect on the domain organization of the plasma membrane 44 leading to efficient docking as previously speculated 45 . Consistent with earlier key reports using TIRF microscopy, we also found that both chromaffin cell and PC12 cell SVs become restricted in their lateral movement following stimulation, indicating that they are undergoing docking 34,35 .…”
Section: Discussionmentioning
confidence: 93%
“…We also measured fluxes between the cytoplasm and the nucleus and the delayed communication caused by the passage through the nuclear pore complex [7,16]. Other successful applications of the pCF approach have been reported by other labs [11,[17][18][19][20]. However, all previous work was aimed at detecting the existence of correlated fluctuations between two distant points without constructing an image of all correlated points.…”
Section: Introductionmentioning
confidence: 99%